Research on Development of Agricultural Geographic Information Ontology - Yong-qi HUANG; Wei-hong CUI; Yang-jian ZHANG; Gao-yan DENG (Journal of Integrative Agriculture, 2012)
This paper first analyzes the reason that agricultural geographic information gives rise to semantic heterogeneity and solution thereof. Although OWL (web ontology language) is the standard of ontology representation language in semantic web, it is insufficient in representing spatial characteristics, especially spatial relationship. Consequently it is pointed out to build geo-ontology by virtue of three theories such as mereology, location theory and topology in this paper. This paper introduces mereology, location theory and topology, and then discusses how to adopt these three theories to build geo-ontology. The outcome of experiment shows that solution put forward by this paper is feasible.